Family legacy: contrasting diversity–elevation relationships on a coastal Atlantic Forest mountain system - de Andrade Kamimura, Vitor [UNESP]; Marcusso, Gabriel Mendes [UNESP]; Sabino, Gabriel Pavan [UNESP]; Assis, Marco Antonio [UNESP]; Joly, Carlos Alfredo; de Paula Loiola, Priscilla [UNESP] (Springer Nature, 2022)
Unveiling the ecological processes driving diversity and its relationship to the environment remains a central goal in ecological studies. Here, we investigated the elevation effect on plant beta-, phylogenetic and alpha-diversity patterns in the coastal Atlantic Forest, considering two scenarios: excluding one basal clade (tree ferns), which are usually neglected in diversity analysis, and depicting the patterns of the five richest families. To do so, we compiled a forest dataset with 22,236 individuals (trees, palms, and tree ferns) from 17 plots in southeastern Brazil. We found significant phylogenetic and species rates of turnover along the elevational gradient; however, species dissimilarities were higher than phylogenetic dissimilarities between communities. Alpha phylodiversity showed a monotonic decrease with increasing elevation, including or not tree ferns, while the phylogenetic structure was highly affected by the inclusion of tree ferns. We found that the unimodal species diversity pattern of the whole community emerged from differences among the species distributions of the richest families (e.g., Myrtaceae, Lauraceae, and Fabaceae), while phylogenetic diversity seemed to be gradually filtered by elevation. The higher species diversification within families and their different diversity patterns might support the idea of different ecological strategies leading to a high species co-occurrence in Tropical Forests. Thus, we show that the intricated effects of elevation on species assemblages can be better assessed using both ecological and evolutionary approaches, stressing the importance of species selection in diversity analyses. These results should be considered in conservation planning, since focusing only on greater diversity for the whole community may not encompass the high diversity of all Tropical Forest families.
Keywords: Atlantic forest; Beta-diversity; Ecological processes; Elevational gradient; Phylogenetic diversity; Species conservation